Respostas

2014-07-10T10:53:16-03:00
2X² = x * 6
2X² - X -6=0

Δ= (-1²) -4.2. (-6)
Δ= 49

x =  1 + ou -√49
              2.2
x' =   1 + 7      ==> x'  =>  8  = 2 
          4                           4                          
 x"= - 1 -7       ==>x " =>  -8  = -2
          4                           4
Resolvendo a equação de segundo grau obtemos x=  -2 ou x que é igual a  2

 
2014-07-10T10:57:32-03:00
O enunciado diz que 2x²=6x
então 2x²-6x=0 ou 2x*(x-3)=0 assim ou 2x=0 ou x-3=0
se 2x=0 x=0
se x-3=0  x=3
resposta { 0 ; 3 }
provando 2* 3² = 6 * 3 ou 2 * 9 = 18 ou 18=18
                0* 0² = 6 * 0  ou 0 = 0